2020
DOI: 10.1097/md.0000000000019429
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photodynamic therapy and periodontal treatment in patients with gingivitis and fixed orthodontic appliances

Abstract: It is known that the presence of orthodontic brackets predisposes for a change in the biofilm, facilitating the development of gingivits. The sites are difficult to access with a toothbrush and periodontal curette, worsening inflammation, in addition, a gingival hyperplasia is associated with poor hygiene. The objective of this study is to evaluate the impact of photodinamyc therapy (PDT) as an adjuvant treatment, considering clinical immunoregulatory and microbiological parameters. This randomized, controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…As in that clinical trial, the combination of PDT and photobiomodulation therapy accelerated the healing process after oral mucositis, reducing the remission time from 15 to 11 days (Pires Marques et al, 2020). Clinical trials of pulpitis (da Mota et al, 2015), periapical periodontitis (Moreira et al, 2015), oral leukoplakia ), peri-implantitis (Al Habashneh et al, 2015, and adverse biofilm changes caused by orthodontic brackets (Rosa et al, 2020) showed that PTD was more effective than traditional treatments. However, further clinical trials are required to establish whether PTD can be used as an alternative mechanical debridement process in the prevention of oral infectious diseases (Javali et al, 2019).…”
Section: Photodynamic Therapymentioning
confidence: 93%
“…As in that clinical trial, the combination of PDT and photobiomodulation therapy accelerated the healing process after oral mucositis, reducing the remission time from 15 to 11 days (Pires Marques et al, 2020). Clinical trials of pulpitis (da Mota et al, 2015), periapical periodontitis (Moreira et al, 2015), oral leukoplakia ), peri-implantitis (Al Habashneh et al, 2015, and adverse biofilm changes caused by orthodontic brackets (Rosa et al, 2020) showed that PTD was more effective than traditional treatments. However, further clinical trials are required to establish whether PTD can be used as an alternative mechanical debridement process in the prevention of oral infectious diseases (Javali et al, 2019).…”
Section: Photodynamic Therapymentioning
confidence: 93%
“…The dye is used for example systemic for the treatment of methaemoglobinemia [16] , septic shock [17] , as an antimalarial agent [18] , as a neuroprotective drug [19] , in local application in colonoscopy [20] , for visualization of organ structures during surgery, for antimicrobial photodynamic therapy in dentistry [21] and for photo-deactivation of viruses in human fresh plasma [ 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…We have not found in the literature any other data on the general lowering of the periodontal pathogenic load using the water jet. Some recent studies have proposed other ways to reduce the bacterial load during orthodontic treatment, such as photobiomodulation, photodynamic therapy, and probiotics [24][25][26][27][28], but the use of a water jet is easier in our opinion overall for the patient. It also seems that the use of the eco-friendly non-electric device is even more performing for this purpose.…”
Section: Resultsmentioning
confidence: 99%